Propuesta de diseño de un puente de sección compuesta sobre el río Alao - Bartra Cordova, Jim Vladimir (2012)
This work is aimed at the analysis and design of a bridge of composite section, which takes place in the town of San Martín de Alao about the river that bears the same name; inaccessibility is the main problem to transport agricultural products to the markets of consumption, in this area that has been severely affected by social as terrorism and drug-trafficking problems. There is a vehicular bridge that joins the production centres, being the only transportation with mules or walk by people who have their farms in this sector and to the village of San Martín de Alao access finally crossing the river San Martin Alao; In addition, the lack of a management tool to fix it. First work with the geometry assessment began both Board, beams and brackets; It has been applied all the knowledge imparted in the University academic...